(3JGQjN GdESdGe hWHbGJ GdeTGgjQ hGdCYdGes - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s ((3SdjeGf Hf YHO Gddg Hf eMeO Hf YHO GdhgGH s)
(3ChdgG (B:s
(3GdWHbI GdKGefI hGdYTQhf SfI EMOi hSHYjf heG Hjf ajgG Jhai YHGS GdOhQi hYHO GdQMef Hf eMeO Hf efUhQ s
(3BNQgG (B:s
(3GHh LYaQ GHf eGgGJ GdQGRi SeY gTGe Hf YeGQ GHh GdTjN cGf Ydi QCS GdKdGKeGjI s
(3HgG fXGe GdJYbjHIs
(3fbdJ gPg GdfSNI ef fSNI cJHgG GHf MLQ GdYSbdGfi hgh fbdgG ef eShOI GdeUfas
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
Keywords: (3GdJGQjNs